2016
DOI: 10.1002/ldr.2601
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fluxes from Different Pools in a Mined Area under Reclamation in Minas Gerais State, Brazil

Abstract: Despite the benefits of grass cultivation and organic fertilization in mining areas undergoing reclamation, these practices may be associated to CO2 emissions and soil organic matter (SOM) losses by priming effect. In the present study, we evaluated the changes on SOM pools and C–CO2 emissions in a bauxite‐mined area under reclamation fertilized with poultry litter (PL) (0, 10, 20, and 40 Mg ha−1) and cultivated with Brachiaria brizantha. Increases of about 3·5 times in the soil labile C were observed 1 year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Other studies have shown that the supply of fresh C and high N fertilization can destabilize subsoil C because of priming effects (Fontaine et al, ; Khan et al, ; da Silva Oliveira et al, ). Recent findings also indicate that microbial community composition can strongly change with N fertilization (Kuslien et al, ; Fanin et al, ) and that microbial activity governs the integration of new C‐input into the soil (Lange et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the supply of fresh C and high N fertilization can destabilize subsoil C because of priming effects (Fontaine et al, ; Khan et al, ; da Silva Oliveira et al, ). Recent findings also indicate that microbial community composition can strongly change with N fertilization (Kuslien et al, ; Fanin et al, ) and that microbial activity governs the integration of new C‐input into the soil (Lange et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying the progress or the effectiveness of any reclamation effort is often difficult given that many soil properties (e.g., SOM) generally require long timescales to exhibit measurable changes. Thus, the extent by which reclamation of degraded lands progresses must be based on the monitoring and evaluation of soil quality indicators (Oliveira et al, ; Shrestha & Lal, ; Tesfahunegn, ). Although identifying possible synergies among distinct soil quality indicators is desirable, assessing such interactions is rather challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, phospholipid fatty acids (PLFAs) analyses have been used to obtain the profiling of the active microbial community in soils ( Willers et al., ; Schmidt et al., ). Thus, PLFAs analyses could help to obtain an assessment of the impact of mining and soil stockpiling on the microbial community ( Birnbaum et al., ), and also an assessment of the response of soil microbes to reclamation practices ( Narendrula‐Kotha and Nkongolo , ). This also would allow the identification of microbes most sensitive to the impact of mining or those most responsive to the reclamation practices applied.…”
Section: Introductionmentioning
confidence: 99%
“…This is because stockpiled topsoil may store viable seeds of the former vegetation and also might work as a source of microbial inoculum during land reclamation (Sheoran et al, 2010). Subsequent improvements in soil structure can be achieved by building terraces to reduce erosion and increase water infiltration rates (Oliveira et al, 2017). Following improvements in soil structure, soil fertility also should be improved by mineral and organic fertilizations, either isolated or in combination (Hu et al, 2015;Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation